Pengaruh Home Visit Method Terhadap Hasil Belajar Luring di Masa Pandemi COVID-19 Pada Mata Pelajaran Al Qur’an Hadits (Studi Kasus Siswa Kelas VIII MTS Jam’iyah Mahmudiyah Tanjung Pura Langkat) - Satria Wiguna, Muamar Al Qadri (Continuous Education: Journal of Science and Research, 2021)
The Home Visit Method is a learning method that can be used during the Covid-19 pandemic. Various obstacles that hinder the implementation of online learning, namely poor network connection, and the lack of online learning facilities such as cellphones and internet quotas as well as the ability of students to use android mobile phones. so that the MTS Jam'iyah Mahmudiyah Tanjung Pura Langkat school implements an offline learning policy, where teachers conduct offline learning by visiting students from house to house in each group. This type of research is quantitative with a case study approach. The data collection method is done through observation, questionnaires and documentation. The population in this study were students of class VIII MTS Jam’iyah Mahmudiyah and the research sample was 48 students. The results of these findings are that there is an effect of the s home visit method on the learning outcomes of the class VIII students of MTs Jam'iyah Mahmudiyah Tanjung Pura Langkat with a total presentation of 64.58% and in the moderate category on the learning outcomes of Al Qur'an Hadith which is carried out continuously offline. The home visit method process is an alternative to learning during the Covid-19 pandemic.